Disputing Denied Downward Transfer-Pricing Adjustments - Sandler, Daniel; Watzinger, Lisa (Canadian Tax Journal/Revue fiscale canadienne, 2019)
This article considers the appropriate forum for disputing a denied downward transfer-pricing adjustment under subsection 247(10) of the Income Tax Act ("the ITA"). It begins by describing various scenarios in which a request for a downward transfer-pricing adjustment may arise, examines the delegation to officials at the Canada Revenue Agency (CRA) of the authority to grant the adjustment, and outlines the CRA's administrative practice on when to grant such adjustments. It then explores whether the Federal Court or the Tax Court of Canada is the appropriate forum to adjudicate a denied downward transfer-pricing adjustment. For disputes under the ITA, the division of jurisdiction between the two courts is generally well defined. The Tax Court has the exclusive jurisdiction to determine the correctness of an assessment whereas the Federal Court has the exclusive jurisdiction to review discretionary decisions of the minister of national revenue or officials at the CRA to whom the minister's powers have been delegated. This jurisdictional divide is less clear for disputes in respect of a denied downward transfer-pricing adjustment. Subsection 247(10) is the only provision in the ITA under which the correct determination of a taxpayer's income is subject to ministerial discretion. The exercise of ministerial discretion suggests that the appropriate forum to dispute a denied transfer-pricing adjustment is the Federal Court. However, subsection 247(11) specifies that the mechanisms for resolving all transfer-pricing disputes under part XVI.1 of the ITA are through the objection and appeal process in part I of the ITA. The language of subsection 247(11), coupled with its legislative history, the restrictions on the Federal Court's jurisdiction, and practical considerations regarding transfer-pricing disputes, all suggest that the Tax Court is the appropriate forum to consider a denied downward transfer-pricing adjustment. Historical case law from the Exchequer Court supports this conclusion. However, there are scenarios in which a denied downward transfer-pricing adjustment may not result in a notice of assessment being issued, and therefore no clear right of appeal to the Tax Court may exist. To ensure that the Tax Court has the jurisdiction to review all denied downward transfer-pricing adjustments, and not only those that result in an assessment, the authors recommend that part XVI.1 of the ITA be amended to include language requiring the minister to issue an assessment in all cases in which a downward transfer-pricing adjustment is denied.